Pengaruh Permainan Tradisional Engklek Terhadap Perkembangan Kognitif Anak Usia 5-6 Tahun - Dwi Ana Pertiwi; Siti Fadjryana Fitroh; Dewi Mayangsari (Universitas Trunojoyo Madura, 2018)
This study aims to determine the effect of traditional games on children cognitive development aged 5-6 years in TK Tarbiyatul Athfal Jaddih, Socah District Bangkalan rege. The game is able to increase affiliation with peers, reduce stress, and improve cognitive development. This game has been proved to increase affiliation with peers, reduce the pressure, and improve children cognitive development. This “englek” traditional games is utilized to stimulate cognitive development in the naming of numbers 1-20 and match numbers with symbols of numbers. This research employed quantitative method with Pre-experimental approach in the form of one group pretestposttest. Subjects in this study were 11 students aged 5-6 years in kindergarten Tarbiyatul Athfal. The data collection was carried out by conducting observation and documentation in the form images of the activities and daily lesson plan. Data analysis was executed by conducting statistical analysis technique of parametris in the form of t-test with data gathered from the result of pretest and posttest. The results obtained at the pretest, there were 2 children have low score and 9 children have been successfully on middle score. The Posttest was carried after giving treatment using “englek” traditional game found 2 children started to grow, 5 children developed as expected, and 4 children developed very well. The result of t-test showed that the value t count is -5,83 and t table 2,086, then -2,086 -5,83 so that Ha was accepted. This finding shows that there is a significant effect of